DOP10 Persistent sonographic Inflammation as a predictor of clinical complications in patients with Crohn's Disease. (27th May 2021) - Vaughan, R; Tjandra, D; Patwardhan, A; Mingos, N; Gibson, R; Boussioutas, A; Christensen, B
Abstract: Background: Transmural healing has emerged as a new treatment target and can be assessed non-invasively with intestinal ultrasound (IUS). We investigated whether the presence of persistent sonographic changes were associated with clinical complications including medication escalation, corticosteroid use, hospitalisation and surgery in Crohn's disease (CD) patients in clinical remission at baseline. Methods: A retrospective study on 212 patients (50% male) with CD who had IUS between August 2017- June 2020 was performed at a tertiary centre. Our analysis included patients in clinical remission at baseline IUS (HBI≤2 or CDAI<150). Patients were excluded if they had disease confined to the rectum, stoma in situ, suboptimal IUS assessment or < 6 months of follow up available. We compared time of medical escalation, corticosteroid use, IBD related hospitalisation or related surgery in patients with and without sonographic inflammation defined as bowel wall thickness (BWT) >3mm and/or hyperaemia on colour doppler imaging, followed for a median of 19 months. We identified factors associated with survival using Kaplan Meier analysis and Cox proportional hazard model. Results: At baseline IUS, 61% of patients had sonographic inflammation. During the follow-up period medical escalation occurred in 51% of patients, corticosteroid use in 23%, hospitalisation in 20% and IBD related surgery in 13% of patients. The presence of sonographic inflammation at baseline was associated with increased risk of medical escalation (p=0.0057), corticosteroid use (p=0.037), hospitalisation (P=0.0085) and surgery (P=0.0062) (Figure 1 A-D). On multivariable analysis only maximal BWT significantly predicted medical escalation (HR 1.22 (1.02–1.46), P=0.0268). The presence of hyperaemia at baseline IUS was significantly associated with corticosteroid use (HR 2.20 (1.13–4.28), P= 0.02). No sonographic parameter predicted the need for IBD related hospitalisation or surgery. Baseline immunomodulator use and stricturing (B3) phenotype was significantly associated with surgery (HR 3.59 (1.22–10.54), P=0.02, HR 4.01 (1.14–14.03), P=0.03, respectively). Figure 1: Kaplan-Meier analysis of the effect of sonographic healing vs sonographic inflammation. A) Medication escalation-free survival. B) Corticosteroid-free survival. C) Hospitalisation-free survival. D) Surgery-free survival. Conclusion: In CD patients in clinical remission, persistent sonographic inflammation can be used as a non-invasive marker of increased risk for clinical complications.